Role of Herbaceous Vegetation in Habitat Utilization by Critically Endangered Great Indian Bustard Ardeotis Nigriceps (Vigors) in the Indian Thar Desert - Bhardwaj, Gobind Sagar; Anoop, K. R.; Sharma, Prerna; Kumar, Suresh (Indian Forester, 2017)
With an objective to enhance the inviolate area, fresh closures were made adjacent to old closures in Thar desert landscape as part of managerial inputs based on in situ conservation guidelines for critically endangered great Indian bustard Ardeotis nigriceps (Vigors). This newly enclosed area was partly mowed and ploughed just before the onset of rains in July which resulted in profuse regeneration of herbaceous vegetation. Preference for these newly made closures by the bustard was noted as compared to old closures. In order to understand causes of such preference, the vegetation of both old and freshly made closures was compared. High richness and abundance of ephemerals and low height of herbaceous vegetation in newly made closures providing better opportunities of feed and enhanced sight distance to detect approaching predators attracted more number of great Indian bustard. Mowing and ploughing the open areas in mosaic pattern breaks the crust laden hard surface allowing regeneration of herbaceous vegetation that improves the habitat for the species. Carrying out this activity annually just before the onset of rains without disturbing the local sewan Lasiurus scindicus and other perennial grasses, shrubs and trees of old closures of bustard range areas emerged as a key management strategy for in situ conservation of great Indian bustard in the Indian part of Thar desert.